Inequalities in hospital admission rates for unintentional poisoning in young children. Issue 3 (2nd June 2006) - Groom, L; Kendrick, D; Coupland, C; Patel, B; Hippisley-Cox, J
Abstract : Objective: To determine the relationship between deprivation and hospital admission rates for unintentional poisoning, by poisoning agent in children aged 0–4 years. Design: Cross sectional study of routinely collected hospital admissions data. Setting: East Midlands, UK. Participants: 1469 admissions due to unintentional poisoning over two years. Main outcome measure: Hospital admission rates for unintentional poisoning. Incidence rate ratios (IRRs) comparing hospital admission rates for poisoning in the most and least deprived electoral wards. Results: Children in the most deprived wards had admission rates for medicinal poisoning that were 2–3 times higher than those in the least deprived wards (IRR 2.49, 95% CI 1.87 to 3.30). Admission rates for non-medicinal poisoning were about twice as high in the most compared to the least deprived wards (IRR 1.77, 95% CI 1.19 to 2.64). Deprivation gradients were particularly steep for benzodiazepines (IRR 5.63, 95% CI 1.72 to 18.40), antidepressants (IRR 4.58, 95% CI 1.80 to 11.66), cough and cold remedies (IRR 3.93, 95% CI 1.67 to 9.24), and organic solvents (IRR 3.69, 95% CI 1.83 to 7.44). Conclusions: There are steep deprivation gradients for admissions to hospital for childhood poisoning, with particularly steep gradients for some psychotropic medicines. Interventions to reduce these inequalities should be directed towards areas of greater deprivation.